A new species of Acianthera (Pleurothallidinae, Orchidaceae) from Brazil - Ponert, Jan; Chumová, Zuzana; Mandáková, Terezie; Trávníček, Pavel (Phytotaxa, 2019)
Acianthera sudae is newly described based on cultivated material from Brazil. It belongs to section Cryptophoranthae and differs from all others in this group by the larger flowers and sepals fused apically for more than half length, and a green-brown abaxial side of sepals with purple dots. Chromosome number (2n = 40) and genome size estimation (1C-value = 1.18 pg) is provided and its phylogenetic placement under the genus is supported with reconstruction of a molecular phylogeny using nuclear ribosomal ITS.